2020
DOI: 10.1155/2020/8890917
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Epigenetic Modulators in Pure Chemical Cell Fate Conversion

Abstract: Although innovative technologies for somatic cell reprogramming and transdifferentiation provide new strategies for the research of translational medicine, including disease modeling, drug screening, artificial organ development, and cell therapy, recipient safety remains a concern due to the use of exogenous transcription factors during induction. To resolve this problem, new induction approaches containing clinically applicable small molecules have been explored. Small molecule epigenetic modulators such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…For the treatment of some neurological disorders, subtype-specific neurons should be induced in appropriate regions of the brain ( Smith et al, 2016 ). Recently, it has been proposed that some in vitro chemical-induced stable neurons could be constructed for brains by a three-dimensional (3D) bioprinting technology, which prints biodegradable materials with cells as 3D tissue ( Ho and Hsu, 2018 ; Yuan et al, 2020 ). In 2021, a lab bioprinted MSC-derived neural tissues successfully using a fibrin-based bioink and the RX1 bioprinter with the aid of SB431542, LDN-193189, purmorphamine, fibroblast growth factor 8 (FGF8), fibroblast growth factor-basic (bFGF), and brain-derived neurotrophic factor (BDNF) ( Restan Perez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the treatment of some neurological disorders, subtype-specific neurons should be induced in appropriate regions of the brain ( Smith et al, 2016 ). Recently, it has been proposed that some in vitro chemical-induced stable neurons could be constructed for brains by a three-dimensional (3D) bioprinting technology, which prints biodegradable materials with cells as 3D tissue ( Ho and Hsu, 2018 ; Yuan et al, 2020 ). In 2021, a lab bioprinted MSC-derived neural tissues successfully using a fibrin-based bioink and the RX1 bioprinter with the aid of SB431542, LDN-193189, purmorphamine, fibroblast growth factor 8 (FGF8), fibroblast growth factor-basic (bFGF), and brain-derived neurotrophic factor (BDNF) ( Restan Perez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased intracellular levels of cAMP by Forskolin provide neurotrophic effects, reduce oxidant stress injury, and improve cellular survivability ( Xu et al, 2019 ). It has also been found that small molecules that target the cAMP/PKA pathway can overcome the interference of in vivo environment on transdifferentiation ( Yuan et al, 2020 ).…”
Section: Mechanisms Of Small Molecules Induced Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to develop transgene-free reprogramming methods, neuronal reprogramming in glioma was recently induced with ROCK and mTOR inhibitors ( 199 ). Alternatively, Yuan et al induced a similar conversion with a small compound cocktail composed of forskolin, ISX9, DAPT, CHIR99021, and I-BET 151 ( 200 ).…”
Section: Modifying the Cell Fate Of Cancer Cellsmentioning
confidence: 99%